Size-controlled preparation of gold nanoclusters stabilized by high-viscosity hydrophilic polymers using a microflow reactor - Setsiri Haesuwannakij (2018)
Gold nanoclusters stabilized by high-viscosity hydrophilic polymers such as poly(N-vinyl-2-pyrrolidone) (K-90) (Au:PVP K-90) and star-shaped polymers (Au:star poly(MOVE) 200 ) were prepared in a continuous flowing process using a microflow reactor. Two types of metal/stainless steel-free microflow reactors (techno-applications COMET X-1 and Sigma-Aldrich type S02) were selected to avoid contamination with other metals. The resultant Au:PVP(K-90) and Au:star poly(MOVE) 200 clusters were significantly smaller with a narrower size distribution than those prepared by the batch process. Graphical Abstract: [Figure not available: see fulltext.]. © 2013 Springer-Verlag Wien.